Determination of oxidative stress level and antioxidant enzyme activities in biathlon athletes and sedentary athletes - Birinci, Ceyhun (Progress in Nutrition, 2022)
Study Objectives: This study aimed to compare oxidative stress levels and enzyme activities in biathlon skiers and sedentary athletes. Methods: A total of 30 participants, 15 biathlon athletes, and 15 sedentary athletes, were included in the study. The athletes were not subjected to a training program but were asked to refrain from eating or drinking after 10:00 PM the day before the samples were taken. Blood samples were taken from the participants after they were informed about the tests. SOD, CAT, and GPx enzyme activities, which are among the lipid peroxidation products, MDA, and antioxidant enzymes, were evaluated spectrophotometrically. Results: It was showed that SOD (p˂0.001), CAT (p˂0.01), and GPx (p˂0.001) enzyme activities were higher in the biathlon athletes compared to those of the sedentary athletes and that the level of MDA, an important lipid peroxidation product, was lower in the biathlon group than in the sedentary group (p˂0.001). Conclusion: As a result, SOD, CAT, and GPx enzyme activities, which are among the lipid peroxidation products of MDA and antioxidant enzymes, were evaluated spectrophotometrically. It was determined that MDA level, which is among the important lipid peroxidation products, decreased in the biathlon group and that SOD, CAT, and GPx enzyme activities were increased in the biathlon group compared to the sedentary group.